Navigating the Sea of Information: Effective Communication Strategies in the Digital Era - Pasaribu, T B Reinhard; Anjani, Dana Alfi; Ramadhan, Rahayu Indah; Zulkarnain, Iskandar (Universitas Mercu Buana, 2025)
An ocean of information is a condition that society must face, especially in the digital era, where access to information can be obtained easily. Information overload has become inevitable. Unfortunately, this ease of access is not accompanied by the community's ability to engage in digital literacy. Even though the digital literacy rate researched by the Ministry of Communication and Information increases yearly, Indonesia's digital literacy rate still lags behind other Asian countries. This article attempts to provide an understanding of technological advances that have implications for easy access to information which requires people to communicate effectively. This article is packaged with a literature study method using various research related to effective communication, information dissemination, and community digital literacy. Through this article, it can be concluded that a qualified communication strategy is needed for individuals to be able to deal with information overload and navigate any information obtained through digital platforms. Developing communication skills and applying ethics in cyberspace is a necessity so that individuals can navigate the sea of information in today's digital era.